DicomBrowser: Software for Viewing and Modifying DICOM Metadata. - Archie, Kevin; Marcus, Daniel (Journal of Digital Imaging, 2012)
Digital Imaging and Communications in Medicine (DICOM) is the dominant standard for medical imaging data. DICOM-compliant devices and the data they produce are generally designed for clinical use and often do not match the needs of users in research or clinical trial settings. DicomBrowser is software designed to ease the transition between clinically oriented DICOM tools and the specialized workflows of research imaging. It supports interactive loading and viewing of DICOM images and metadata across multiple studies and provides a rich and flexible system for modifying DICOM metadata. Users can make ad hoc changes in a graphical user interface, write metadata modification scripts for batch operations, use partly automated methods that guide users to modify specific attributes, or combine any of these approaches. DicomBrowser can save modified objects as local files or send them to a DICOM storage service using the C-STORE network protocol. DicomBrowser is open-source software, available for download at .